SUSUT BOBOT BERAS SELAMA PENYIMPANAN KARENA RESPIRASI - Nurrahman ,- (JURNAL LITBANG, 2005)
After post harvest, agriculture product is still physiology change. Biochemical reactions in commodity of agriculture was accident until destroying and deterioration, so that lost in storage process. Matter lost can be accident by respiration. Respiration is biochemical reactions in agriculture product that involve activity of enzyme. Product of respiration is carbon dioxide, water and energy. Velocity of respiration was influent by water contains, temperature, humidity, composition of air, saturated boiling pressure and condition of matter. Water contains is factor very important in matter lost by respiration. Dry matter lost by respiration in storage process was not more than 0.8 percent. Keywords: Respiration, matter lost, storage and rice